Dynamic Mathematical Model Framework of Complex Utility and Logistics System Interactions Using Object-Oriented Approach for Forward Operating Bases. Issue 2 (2nd April 2016) - Poreddy, Bhanuchander R.; Corns, Steven; Long, Suzanna; Soylemezoglu, Ahmet
Abstract: Forward operating bases are temporary military contingency bases established to support and facilitate tactical operations on foreign soil. Operational and logistical inefficiencies, excessive resource demands, and increased costs are some of the issues caused by poor initial planning of contingency bases. In this article, a modeling method is introduced to increase planning capabilities for base camps using an object-oriented approach. The model addresses issues faced by the Department of Defense related to unexpected second-, third-, and higher-order effects observed on base camps, determined to be caused by the interactions between the base camp utility systems. The model is based on a coupled mathematical system of equations that captures the relationships between various base camp subsystems and their respective inputs and outputs. Subsystems are objectified and their various inputs and outputs are parameterized to solve the system of equations simultaneously each time there is a change in base camp design.